Nanovaccine‐Based Strategies to Overcome Challenges in the Whole Vaccination Cascade for Tumor Immunotherapy. Issue 28 (26th March 2021) - Qin, Lin; Zhang, Huilin; Zhou, Yang; Umeshappa, Channakeshava Sokke; Gao, Huile
Abstract: Nanovaccine‐based immunotherapy (NBI) has received greater attention recently for its potential to prime tumor‐specific immunity and establish a long‐term immune memory that prevents tumor recurrence. Despite encouraging results in the recent studies, there are still numerous challenges to be tackled for eliciting potent antitumor immunity using NBI strategies. Based on the principles that govern immune response, here it is proposed that these challenges need to be addressed at the five critical cascading events: Loading tumor‐specific antigens by nanoscale drug delivery systems (L); Draining tumor antigens to lymph nodes (D); Internalization by dendritic cells (DCs) (I); Maturation of DCs by costimulatory signaling (M); and Presenting tumor‐peptide‐major histocompatibility complexes to T cells (P) (LDIMP cascade in short). This review provides a detailed and objective overview of emerging NBI strategies to improve the efficacy of nanovaccines in each step of the LDIMP cascade. It is concluded that the balance between each step must be optimized by delicate designing and modification of nanovaccines and by combining with complementary approaches to provide a synergistic immunity in the fight against cancer. Abstract : Nanovaccine‐based immunotherapy has received significant attention recently since it can trigger antigen‐specific immunity and establish long‐term immune memory for preventing tumor recurrence. However, there are still many challenges to be addressed for eliciting potent immunity. This review provides a detailed overview of emerging nanovaccine‐based strategies to improve the efficiency of each process within the challenges in the whole vaccination cascade.